Exploring The Basics of Phonology: A Comprehensive Guide - Tisya Amalia Putri Sitorus; Aliyah Fidiani; Icha Fahriza; Futri Dina Wardiah; Yani Lubis (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
The aims of this research are to help students new to English phonology understand its fundamentals. The study employs a literature review methodology to explore the field of English phonology. It addresses key topics for beginners, including the basic units of sound (phonemes) and their variations (allophones). The research also discusses vowel and consonant reduction, which impacts the pronunciation of certain sounds. Finally, it provides an overview of how consonant and vowel sounds are grouped based on their characteristics. By studying these elements, beginners can enhance their pronunciation, recognize different sound patterns, and improve their overall communication skills in English.